1999
DOI: 10.1076/clin.13.3.249.1746
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Functioning in Depressed Versus Nondepressed Participants with Alzheimer's Disease

Abstract: Differences in cognitive functioning between participants with Alzheimer's Disease (AD) reporting depressive symptomatology (AD-Dep; n = 37) and a control group of nondepressed participants with AD (AD-Con; n = 98) were investigated based on hypothesized impairments of attention/concentration, psychomotor speed, and simple motor speed. Groups did not differ in age, education, overall severity of dementia, auditory comprehension, or use of psychotropic medications. AD-Dep participants performed significantly mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…As previously noted, although past studies have often attempted to use standardized procedures in diagnosing AD and depression in the elderly, little success has been reported in obtaining a clinical profile of cognitive abilities for both populations (Breen et al, 1984;Lopez et al, 1990;Wefel, Hoyt, & Massman, 1999). Our findings suggest that success in this area may be achieved when using theory-based tools, with the WJ-III COG representing a concise and accurate diagnostic tool.…”
Section: Discussionsupporting
confidence: 53%
“…As previously noted, although past studies have often attempted to use standardized procedures in diagnosing AD and depression in the elderly, little success has been reported in obtaining a clinical profile of cognitive abilities for both populations (Breen et al, 1984;Lopez et al, 1990;Wefel, Hoyt, & Massman, 1999). Our findings suggest that success in this area may be achieved when using theory-based tools, with the WJ-III COG representing a concise and accurate diagnostic tool.…”
Section: Discussionsupporting
confidence: 53%
“…As subgroups were rather small, false negative results cannot be excluded in this study. In another study, AD patients with depression performed more poorly on Block design, Digit Symbol and speeded motor programming, but performed better on a test of logical memory than non-depressed AD-patients (Wefel et al, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to the issues inherent in diagnosing depression in AD, methodological flaws and inconsistencies underlie the contradictory findings and have fueled the debate surrounding this topic. The literature provides evidence for the negative impact of depression on domains including general cognition [19], full scale IQ [20], measures of dementia severity, working memory, processing speed [21], attention, motor functioning [22], and visuospatial perception and construction [12,22]. Other investigators have found no cognitive differences between AD patients with and without depressive symptoms [23,24].…”
Section: The Impact Of Depression and Apathy On Cognition In Admentioning
confidence: 99%